Virtual Power Plant and Multi-prosumer Hybrid Game Strategy Based on Energy Sharing - QI Lei, GAO Yang, AI Qian (Dianli jianshe)
When constructing new power systems，the increasing number of prosumers with varying sizes，such as microgrids and commercial buildings，has to be considered. A virtual power plant formed by the aggregation and interconnection of such prosumer clusters can collaboratively optimize flexible resources and improve the overall efficiency of the cluster through power interactions and power mutual aid. To realize the coordinated operation of multiple prosumers，this study proposes a mixed game strategy between virtual power plant operators and multiple prosumers. First，a master-slave game model of virtual power plant operators and multiple prosumers is constructed. The virtual power plant operator （master） dynamically adjusts the electricity prices，and the prosumers （slave） follow. Considering the uncertainty of new internal energy sources，an optimal dispatch is conducted based on distributed robust opportunity constraints. Subsequently，a multi-prosumer cooperative game model is constructed based on the scheduling strategy and transaction results of the master-slave game. Further，a cooperative income distribution strategy based on energy contributions is proposed to achieve a fair and reasonable distribution of income from multi-prosumer cooperation alliances. Finally，the rationality and superiority of the proposed hybrid game strategy are verified through a numerical example analysis.